DZIKR AND MEDITATION IN TASHAWWUF: Spiritual Disciplines, Psychological Benefits, and Their Contemporary Relevance - Afifi, Mansur; Fattah, Abdul; Mareta, Mira; Fakhri, Mohammad (State Islamic University North Sumatra, 2025)
Dzikr (remembrance of Allah) and meditation are core spiritual practices in Islam that support inner peace and personal transformation. Grounded in the Qur’an and developed within tashawwuf (Sufism), they aim to purify the self (tazkiyah al-nafs), deepen God-consciousness, and cultivate spiritual tranquillity. This study explores the relevance of dzikr and meditation by integrating Islamic spiritual perspectives with contemporary psychological and mental-health insights. Using a qualitative–descriptive method, data were obtained through literature analysis and participatory observation in dzikr and meditation gatherings, supplemented by informal interviews. The results show that these practices enhance spiritual well-being by fostering gratitude, emotional balance, and awareness of the Divine, while also producing measurable psychological benefits such as reduced stress and increased resilience. The study concludes that dzikr and meditation remain highly relevant for promoting holistic well-being and providing accessible pathways to balance and meaning in modern life.